Improving knowledge of doctors and paramedics through effective bone procurement workshop: A cognitive approach - Mohd, Suhaili; Yusof, Norimah; Lai, Lee Lee; Hossain, Md. Golam; Ramalingam, Saravana; Hamid, Suzina Sheikh Ab; Ng, Wuey Min; Mansor, Azura (BMC, 2019)
Background: Procurement of bone allograft must be performed by trained personnel. Improper handling and lack of knowledge during bone procurement will lead to contamination hence jeopardizing quality of the procured bones and expose bone recipients to risks of infection in post-operative phase. Bone procurement workshop is the fundamental training programme to enhance skill among personnel who has been or will be involved in bone procurement. This study evaluated the effectiveness of the workshop contents including teaching materials by assessing the knowledge on bone procurement among the participants before and after the workshop. Methods: Bone procurement workshop was held for 2 days for doctors and paramedics. The knowledge on bone procurement was evaluated in pre- and post-assessments by answering self administration questionnaire before and after the workshop, respectively. Results: A total of 50 participants comprised of doctors and paramedics attended the workshop however only 15 (55.6%) doctors and 12 (44.4%) paramedics completed the assessments. Overall, the mean total score for the post-assessment (61.4%) was significantly higher (p < 0.05) than that of the pre-assessment score (32.2%). The mean values of correct responses for the post-assessment was significantly higher (p < 0.05) than that of the pre-assessment in all five topics given during the workshop. The correct responses for the pre- and the post- assessments in the respective group of the doctors and paramedics were also statistically significant (p < 0.05). In the pre-assessment, the doctors had the highest score in Surgical Approach & Reconstruction (50%) while the paramedics had the highest score in Donor Screening & Selection Criteria (33.3%). In the post-assessment, the doctors had the highest score in Donor Screening & Selection Criteria (70%) while the paramedics in Packaging & Transportation (65.8%). Conclusions: The assessment managed to show that the workshop contents and teaching materials were effective in improving the cognitive knowledge of the personnel who would get involved in bone procurement under the National Donation Programme. © 2019 The Author(s).